Basement Membrane-Based Glucose Sensor Coatings Enhance Continuous Glucose Monitoring in Vivo - Klueh, Ulrike (J Diabetes Sci Technol, 2015)
BACKGROUND: Implantable glucose sensors demonstrate a rapid decline in function that is likely due to biofouling of the sensor. Previous efforts directed at overcoming this issue has generally focused on the use of synthetic polymer coatings, with little apparent effect in vivo, clearly a novel approach is required. We believe that the key to extending sensor life span in vivo is the development of biocompatible basement membrane (BM) based bio-hydrogels as coatings for glucose sensors. METHOD: BM based bio-hydrogel sensor coatings were developed using purified BM preparations (ie, Cultrex from Trevigen Inc). Modified Abbott sensors were coated with Cultrex BM extracts. Sensor performance was evaluated for the impact of these coatings in vitro and in vivo in a continuous glucose monitoring (CGM) mouse model. In vivo sensor function was assessed over a 28-day time period expressed as mean absolute relative difference (MARD) values. Tissue reactivity of both Cultrex coated and uncoated glucose sensors was evaluated at 7, 14, 21 and 28 days post–sensor implantation with standard histological techniques. RESULTS: The data demonstrate that Cultrex-based sensor coatings had no effect on glucose sensor function in vitro. In vivo glucose sensor performance was enhanced following BM coating as determined by MARD analysis, particularly in weeks 2 and 3. In vivo studies also demonstrated that Cultrex coatings significantly decreased sensor-induced tissue reactions at the sensor implantation sites. CONCLUSION: Basement-membrane-based sensor coatings enhance glucose sensor function in vivo, by minimizing or preventing sensor-induced tissues reactions.